4x - 2 (3+2x) = -6

4x - 2 (3+2x)+ 6 = 0

4x - 2 (3+2x)+ 6 = 0

4x - 2 (3+2x) = -6

4x - 2 (3+2x)+ 6 = 0

4x - 2 (3+2x)+ 6 = 0

It is a tautology, meaning it is true for all values of x. It is a linear equation with an infinite number of solutions.

The left side expands to

4x + (-2*3) + (-2*2x)

= 4x - 6 - 4x

= x(4 - 4) - 6

= 0x - 6

= -6

Of course, the right side is also -6.

The left side expands to

4x + (-2*3) + (-2*2x)

= 4x - 6 - 4x

= x(4 - 4) - 6

= 0x - 6

= -6

Of course, the right side is also -6.

Didn't find the answer you were looking for?